Shedding light on bifunctional luminescent spin crossover materials - Javed, Mohammad Khurram; Sulaiman, Arshia; Yamashita, Masahiro; Li, Zhao-Yang (Coordination chemistry reviews, 2022)
[Display omitted] •Synergistic luminescent spin crossover (SCO) materials are reviewed.•Strategies used to synthesize luminescent SCO materials are presented.•Challenges for achieving SCO-luminescence synergy in materials are discussed. The spin crossover (SCO) phenomenon has witnessed remarkable progress in applications since it was first discovered almost a century ago. Specifically, materials that exhibit SCO-luminescence synergy have garnered significant interest owing to their excellent potential applications in optoelectronic devices. Over the past two decades, the interplay and synergy between SCO and luminescence have led to the development of an extensively researched field. Thisreview aims to evoke a concise discussion on luminescent SCO materials by presenting an overview that focuses on their luminescence and magnetic properties, strategies for their syntheses,and progress madeover the yearstoward constructing such materials, from nanoscale to long-chain polymers.